UK audit of quantitative thyroid uptake imaging. Issue 7 (July 2017) - Taylor, Jonathan C.; Murray, Anthony W.; Hall, David O.; Barnfield, Mark C.; O'Shaugnessy, Emma R.; Carson, Kathryn J.; Cullis, James; Towey, David J.; Kenny, Bob
Abstract : Aim: A national audit of quantitative thyroid uptake imaging was conducted by the Nuclear Medicine Software Quality Group of the Institute of Physics and Engineering in Medicine in 2014/2015. The aims of the audit were to measure and assess the variability in thyroid uptake results across the UK and to compare local protocols with British Nuclear Medicine Society (BNMS) guidelines. Participants and methods: Participants were invited through a combination of emails on a public mailbase and targeted invitations from regional co-ordinators. All participants were given a set of images from which to calculate quantitative measures and a spreadsheet for capturing results. The image data consisted of two sets of 10 anterior thyroid images, half of which were acquired after administration of 99m Tc-pertechnetate and the other half after administration of 123 I-iodide. Images of the administration syringes or thyroid phantoms were also included. Results: In total, 54 participants responded to the audit. The median number of scans conducted per year was 50. A majority of centres had at least one noncompliance in comparison with BNMS guidelines. Of most concern was the widespread lack of injection-site imaging. Quantitative results showed that both intersite and intrasite variability were low for the 99m Tc dataset. The coefficient of quartile deviation was between 0.03 and 0.13 for measurements of overall percentage uptake. Although the number of returns for the 123 I dataset was smaller, the level of variability between participants was greater (the coefficient of quartile deviation was between 0.17 and 0.25). Conclusion: A UK-wide audit showed that thyroid uptake imaging is still a common test in the UK. It was found that most centres do not adhere to all aspects of the BNMS practice guidelines but that quantitative results are reasonably consistent for 99m Tc-based scans. Abstract : Supplemental Digital Content is available in the text.